Two novel BODIPY–Ru(ii) arene dyads enabling effective photo-inactivation against cancer cells1. Issue 28 (28th July 2015) - Wang, Tianji; Hou, Yuanjun; Chen, Yongjie; Li, Ke; Cheng, Xuexin; Zhou, Qianxiong; Wang, Xuesong
<x xml:space="preserve">Abstract</x> Hybrids of an iodized BODIPY chromophore and a Ru(ii) arene complex lead to novel photoactivated anticancer agents with cytotoxicities more than one order of magnitude higher than cisplatin.